The Effect of Professional Development on Indonesian EFL Teachers' Self-Efficacy - Bachtiar Bachtiar (EDUVELOP, 2019)
This study aims to find out the relationship between teachers’ participation in professional development (PD) and changes in perceived levels of their self-efficacy in the areas of instructional strategy, classroom management, and student engagement. A mixed methods research was used in this study. The findings from this study revealed that there is a relationship between teachers’ participation in PD and changes in perceived levels of their self-efficacy. The findings also revealed that PD was perceived to bring about the greatest change in levels of all participants’ self-efficacy in the area of instructional strategy compared to classroom management and student engagement. The study suggests that one of the characteristics of good quality PD for junior secondary EFL teachers in Indonesia is the content should be based on teachers’ classroom practical needs.